2008
DOI: 10.4141/p06-158
|View full text |Cite
|
Sign up to set email alerts
|

Variation in morphology, plant habit, proanthocyanidins, and flavonoids within a Lottus germplasm collection

Abstract: K. 2008. Variation in morphology, plant habit, proanthocyanidins, and flavonoids within a Lotus germplasm collection. Can. J. Plant Sci. 88: 121Á132. Lotus species collected from a range of geographical locations were evaluated for relationships between plant habit and size, leaf proanthocyanidin (PA) content, flower colour, stem colour, leaf colour, trichome density, and geographic origin. No relationships occurred between leaf PA concentration and morphological trait or collection site. Trichome coverage was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The cyanogenesis defense provides an ideal immediate response to florivores and primary nectar robbers. There are many other examples of high content of defense compounds in flowers, including such classes of metabolites as glucosinolates (Straus et al 2004), cyclic hydroxamic acids (Bravo and Copaja 2002), terpenoids (Tawaha and Hudaib 2012), flavonoids (Gruber et al 2008) and alkaloids (Eichhorn et al 1998). While a meta-analysis of published and unpublished studies did not support the 'optimal defense theory' for defense of flowers by secondary metabolites (McCall and Fordyce 2010), the survey results may be obscured by alternative defense strategies such as indirect defenses, mechanical defenses and When analysed alone, neolinustatin (6) in the flax seeds extracts has an identical retention time as in the mixture of the nectar sample with flax seeds extract (representative chromatograms of n = 3 nectar washes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyanogenesis defense provides an ideal immediate response to florivores and primary nectar robbers. There are many other examples of high content of defense compounds in flowers, including such classes of metabolites as glucosinolates (Straus et al 2004), cyclic hydroxamic acids (Bravo and Copaja 2002), terpenoids (Tawaha and Hudaib 2012), flavonoids (Gruber et al 2008) and alkaloids (Eichhorn et al 1998). While a meta-analysis of published and unpublished studies did not support the 'optimal defense theory' for defense of flowers by secondary metabolites (McCall and Fordyce 2010), the survey results may be obscured by alternative defense strategies such as indirect defenses, mechanical defenses and When analysed alone, neolinustatin (6) in the flax seeds extracts has an identical retention time as in the mixture of the nectar sample with flax seeds extract (representative chromatograms of n = 3 nectar washes).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the total concentration of glucosinolates are higher in petals than leaves of Raphanus sativas (Straus et al 2004); cyclic hydroxamic acids are found in high amounts in the stamen compared to leaves of Acanthus mollis (Bravo and Copaja 2002); monoterpenoids are found in high levels in flowers of Thymus capitatus (Tawaha and Hudaib 2012); proanthocyanidins accumulate in flowers but not leaves of the model legume Lotus japonicus (Gruber et al 2008) and in flowers of white clover (Foo et al 2000); and the alkaloid galanthamine is highly biosynthesized by tissues from ovary walls and flower stalks of Leucojum aestivum (Eichhorn et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Alignment of CT composition with function offers opportunities for exploiting their bioactivities, and germplasm collections offer a rich source of CT variation Klongsiriwet, 2016). Concentrations of CTs vary greatly not only between plant species but also between accessions (Larkin et al, 1997;Mosjidis 2001;Sivakumaran et al, 2004;Gruber et al, 2008;Häring et al, 2008;Lorenz et al, 2010;Grabber et al, 2015;Hixson et al, 2016). Table 1 lists the variation in forage plants: birdsfoot trefoil tends to have the lowest (<5 g 100 g −1 dry matter) and sericea lespedeza and erect canary clover the highest CT concentrations (6-20 g 100 g −1 dry matter).…”
Section: Tannin Variation In Germplasm Collections and Potential For mentioning
confidence: 99%
“…Due to the lack of intraspecific polymorphism for PAs in the herbage and the complexity of the genetic control of this trait, neither classical nor biotechnological-based approaches have succeeded to breed bloat-safe forage legumes within these genus yet (Pang et al 2007;Hancock et al 2012). In stark contrast to Medicago, in which anthocyanin biosynthesis appears to be predominant over PA biosynthesis (Li et al 2016), the Lotus genus presents species polymorphic for the foliar PA trait, and in the leaves that accumulate PAs anthocyanins are absent (Sivakumaran et al 2006;Gruber et al 2008). The widely cultivated tetraploid Lotus corniculatus L. accessions present moderate levels of PAs, whereas the diploid species Lotus tenuis Waldst.…”
Section: Introductionmentioning
confidence: 96%